Quanti sono gli italianismi nel tedesco contemporaneo? - Rovere, Giovanni (Italiano LinguaDue, 2009)
Il contributo, incentrato sul tema dell’italianismo in prospettiva lessicografica tra storia, etimologia e cultura, tocca i problemi della consistenza del prestito italiano in tedesco ( diretto, indiretto, calco, ibridismo, deonomastico, pseudoitalianismo), connessi con quelli delle modalità dell’integrazione. The article focuses on Italianisms from a lexicographical perspective embracing history, etymology and culture and involving issues related to the duration of borrowings from Italian in French, the motives that generated it, the mediating function by which it is characterized, its semantic range, both synchronic and diachronic, and the aspect of derivations.